Asthma in the elderly: an epidemiological survey. Issue 6170 (21st April 1979) - Burr, M L; Charles, T J; Roy, K; Seaton, A
Abstract : A random sample of one in eight people aged 70 and over living at home in a south Wales town was surveyed to establish the prevalence of asthma. Subjects attended a screening clinic, where spirometry before and after an inhalation of salbutamol, skin prick testing, blood count, and sputum examination were carried out and a questionnaire answered. Those in whom asthma seemed at all likely were subsequently examined in detail in a chest clinic. Out of 485 subjects eligible, 418 (86.2%) were screened. Twelve (2.9%) had current asthma, of whom three had not previously been diagnosed as asthmatic and four were being treated but were unaware of the diagnosis. A further 15 (3.6%) had mild asthma or a history of the disease, giving a total prevalence of any history of asthma of 6.5%. Only one of the subjects who did not attend the screening clinic was known to have asthma, suggesting that the overall prevalence did not differ greatly from this figure. It was found that the disease might start or remit at any age. Thus in the elderly current asthma is more prevalent in men than women (5.1% compared to 1.8%) and in terms of spirometry is more severe. Two underlying disease processes may perhaps exist that fulfil criteria for asthma in the elderly, one causing sputum eosinophilia and the other a form of chronic bronchitis with reversible airways obstruction.